Effect Of Tamarind (Tamarindus indica L.) Extract To Histamine Content In Bullet Tuna (Auxis rochei) - Hattu, Nikmans; Latupeirissa, Jolantje; Fransina, Eirene G.; Seumahu, Cecelia A; Latupeirissa, Astrid (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2014)
The research to determine histamine content in bullet of tuna (Auxis rochei) with variation of tamarind (Tamarindus indica L.) extract concentrations and time of marinate has been done. The histamine content is determined quantitatively by using ultraviolet-visible spectrophotometer with the calibration curve method. The result showed that histamine content in bullet tuna marinated in tamarind extract with varied concentrations of 5%, 10%, 15%, and 20% within 10 minutes, are 37.4561, 35.3041, 23.8778, and 22.1186 mg/100 g respectively. While, the concentrations of histamine in bullet tuna marinated in 20% of tamarind extract with variation of 10, 20, 30, 40, and 50 minutes, are 22.2965, 19.7544, 17.6925, 11.5865, and 8.0396 mg/100 g respectively. A qualitatively, visual comparison of colour intensity of samples with reference colour scale of the standard solution concentration can be used to determine concentrations of histamine without the aid of a spectrophotometer.